Antimicrobial Activity of Essential Oils against Staphylococcus and Malassezia Strains Isolated from Canine Dermatitis - Ebani, Valentina Virginia (Microorganisms, 2020)
Staphylococcus spp. bacteria are the most frequently involved agents in canine cutaneous infections. Treatment of these infections is based on antibiotic therapy, that often is not effective because of the antibiotic-resistance of the bacterial strains. Cutaneous staphylococcal infections are often complicated by Malassezia yeasts, that may be resistant to the conventional antifungal drugs. The present investigation was aimed to evaluate the in vitro antimicrobial activity of some essential oils (EOs) in view of a potential cutaneous application. In detail, EOs obtained from lemon verbena (Aloysia triphylla L’Hèr. Britton), cinnamon (Cinnamomum zeylanicum J. Presl), myrrh (Commiphora myrrha (Nees) Engl. var. molmol), lemongrass (Cymbopogon citratus (DC.) Stapf), litsea (Litsea cubeba (Lour.) Pers.), lemon balm (Melissa officinalis L.), oregano (Origanum vulgare L.), savory (Satureja montana L.), and thyme (Thymus vulgaris L.) were assayed against Staphylococcus spp. and Malassezia pachydermatis strains previously isolated from dogs with dermatitis. All EOs were tested by agar disk diffusion and minimum inhibitory concentration methods to verify the antistaphylococcal activity, and by a microdilution method to evaluate the activity against M. pachydermatis. O. vulgare, T. vulgaris, and S. montana showed the best antibacterial activity against all the selected strains, with MICs ranging from 0.29 to 0.58 mg/mL, from 0.58 to 1.16 mg/mL, and from 0.56 to 1.12 mg/mL, respectively, whereas A. triphylla (1.03 mg/mL) and S. montana (1.8 mg/mL) were the most active against M. pachydermatis. After a proper in vivo evaluation, O. vulgare, T. vulgaris, and S. montana EOs could be a promising treatment to combat canine cutaneous mixed infections.